Human insecurity in Nigeria: a case study of Boko Haram from 2009-2019 - Idu, Joy Chioma (Department of Political Studies, 2020)
Human security is an essential aspect of human rights, as it is necessary for every human to feel secured in their community, and country at large. However, human security is frequently threatened by conflict, especially in Africa. Adding to the different challenges that most African states face, conflict contributes immensely towards destabilizing human security. As such, this thesis addresses the destabilized human security situation in Nigeria, by examining the implication of the Boko Haram insurgency. The effects of the Boko Haram insurgency in Nigeria, ranges from political, economic, social, cultural, to environmental. These insecurities have led to the destabilisation of the country and its economy. Although human security is broad, this thesis focuses on the political and socio-economic implications of the Boko Haram insurgency. This includes, but not limited to, poverty and illiteracy, unemployment, poor healthcare service, displacement, national insecurity, and political instability. The thesis argues that the Nigerian government has been unable to defeat the insurgent group due to the increasing rate of corruption in the country, which in turn leads to lack of adequate human and material resources need to win the group. In conducting this research, a literature-based methodology was employed, where secondary data, in the form of books, newspapers, online articles/journals, and reports, that have been written on the topic, were critically analysed to draw up adequate information on the activities of Boko Haram and it implications on the human security of the country.